Pandemic-era Participation in Public Lands Governance: Lessons From the USDA Forest Service - Floress, Kristin; Cohen, Alice (Frontiers in Sustainable Cities, 2022)
Public participation processes influencing National Forest and Grassland management in the United States have shifted significantly because of the global COVID-19 pandemic. Although the United States Forest Service has used virtual participation tools to engage stakeholders and communities in the past, the agency has not primarily relied on virtual techniques and faced challenges in doing so during the pandemic. Forest Service staff are gaining experience conducting virtual public participation and integrating results into land management plans, project implementation, and environmental analyses. Using the concepts of access, standing, and influence from the Trinity of Voice theory, we offer insight into how each has been and can be impacted by virtual versus in-person public participation in federal land governance. Lessons shared in this perspective come from peer-to-peer learning sessions among Forest Service staff in Fall, 2020, and a case from the National Forests in North Carolina is used to provide details about how staff responded to pandemic-related disruptions to public participation. We discuss factors to be considered when using virtual participation methods as well as implications for the future of public participation.